DEVELOPMENT AND EVALUATION OF NANOSPONGE LOADED TOPICAL HERBAL GEL OF WRIGHTIA TINCTORIA - IRIVENTI, PADMINI; GUPTA, N. VISHAL (International Journal of Applied Pharmaceutics, 2020)
Objective: Psoriasis is the most common chronic autoimmune disease. The main objective of the present study was to develop Nanosponge (NS) based Topical gels of Wrightia tinctoria extract using cross-linker and polymer by melting method. It is used in treating Psoriasis. Methods: Phytoconstituents present in the herbal extract were identified by Liquid Chromatography-Mass Spectroscopy (LC-MS) studies. In vitro drug release and Entrapment Efficiency of all NS were determined. The optimized NS were incorporated in the gel to formulate nano topical gel. Evaluation studies like homogenicity, viscosity, spreadability, pH and In vitro studies were carried out for all gel formulations. Results: The prepared gels were transparent, had good viscosity and spreadability. SEM photographs confirmed that the prepared formulation were roughly spherical and porous in nature. In vitro diffusion studies showed drug release of 92.15% in 24 h. Conclusion: From this study it can be concluded that constituents responsible for treating psoriasis are present in the obtained extract and prepared NS based topical gel has significant effect in providing sustained drug release.